2007
DOI: 10.1101/gr.6009507
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mouse Duffy Antigen Receptor for Chemokines (Darc) as a BMD QTL gene

Abstract: It is now well known that bone mineral density (BMD) variance is determined by both genetic and environmental factors. Accordingly, studies in human and animal models have revealed evidence for the presence of several quantitative trait loci (QTL) that contribute to BMD variations. However, the identification of BMD QTL genes remains a big challenge. In the current study, we focused our efforts to identify the BMD candidate gene in chromosome 1 (Chr 1) QTL that was detected from a cross involving high BMD CAST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…33 Mice lacking only endothelial Darc exhibit deficient leukocyte emigration, 27 and recent studies have identified DARC as a major regulator of murine bone mineral density through a role in cytokine-mediated osteoclastogenesis. 34 Although in general recent GWA studies have reported small effect sizes, we found a single variant, DARC rs12075 (Asp42Gly), that explains approximately 20% of the variation in MCP-1 serum concentration, which is considerably greater than all previously known correlates combined. 13 It is notable that DARC is a trans-acting variant and is not on the same chromosome as the gene coding for MCP-1 (CCL2).…”
Section: Variation In Darc Is Associated With Serum Cytokine Levelsmentioning
confidence: 47%
“…33 Mice lacking only endothelial Darc exhibit deficient leukocyte emigration, 27 and recent studies have identified DARC as a major regulator of murine bone mineral density through a role in cytokine-mediated osteoclastogenesis. 34 Although in general recent GWA studies have reported small effect sizes, we found a single variant, DARC rs12075 (Asp42Gly), that explains approximately 20% of the variation in MCP-1 serum concentration, which is considerably greater than all previously known correlates combined. 13 It is notable that DARC is a trans-acting variant and is not on the same chromosome as the gene coding for MCP-1 (CCL2).…”
Section: Variation In Darc Is Associated With Serum Cytokine Levelsmentioning
confidence: 47%
“…It is now known that genetic variations influencing gene expression contribute to differences in peak bone mass in humans (6,14). In our mouse model, we found that haploid insufficiency of Osx in chondrocytes caused delayed skeletal growth reflected by reduced total body length and weight, as well as reduced BMC and BMD in long bones of young mice.…”
Section: Discussionmentioning
confidence: 65%
“…CC and CXC chemokines are potent chemoattractants for eosinophils, basophils, monocytes, and T cell subsets and are believed to be crucial mediators of inflammation in asthma (40,41). DARC has previously been associated with the inflammatory process in prostate cancer (42,43), preeclampsia in women from West Africa (44), and bone mineral density in a murine model (45). Similar to asthma, these clinical conditions exhibit a different prevalence between African Americans and individuals of European descent (46,47), which may also be explained by variations in the exposure stimulating chemokines and/or differences in the function of DARC among these populations.…”
Section: Discussionmentioning
confidence: 99%